2004
DOI: 10.1038/sj.bmt.1704784
|View full text |Cite
|
Sign up to set email alerts
|

Dose-escalated treosulphan in combination with cyclophosphamide as a new preparative regimen for allogeneic haematopoietic stem cell transplantation in patients with an increased risk for regimen-related complications

Abstract: Summary:Treosulphan has recently demonstrated antileukaemic activity and potent haematopoietic stem cell toxicity. Dose-escalated treosulphan (3 Â 12 or 3 Â 14 g/m 2 ) combined with cyclophosphamide (Cy) was chosen for a new preparative regimen before allogeneic haematopoietic stem cell transplantation in 18 patients (median age 44, range 19-64 years) with haematological malignancies, considered ineligible for other myeloablative preparative regimens. Pharmacokinetic studies demonstrated rapid treosulphan plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
78
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 24 publications
8
78
2
Order By: Relevance
“…AUC of the remaining children were in the range of 579-1080 mg/l h (mean 906) and were comparable with the literature data for adult patients. 7 In addition, high value was obtained for child treated with 14 g/m 2 dose. The metabolic acidosis as a result of the methanesulphonic acid formation from treosulfan can cause increasing AUC, because the activation of treosulfan is pH dependent and at pH o6 almost no treosulfan is metabolized.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…AUC of the remaining children were in the range of 579-1080 mg/l h (mean 906) and were comparable with the literature data for adult patients. 7 In addition, high value was obtained for child treated with 14 g/m 2 dose. The metabolic acidosis as a result of the methanesulphonic acid formation from treosulfan can cause increasing AUC, because the activation of treosulfan is pH dependent and at pH o6 almost no treosulfan is metabolized.…”
Section: Discussionmentioning
confidence: 85%
“…[3][4][5][6] In addition, it was demonstrated both in vivo and in vitro that treosulfan reveals an excellent toxicity against all stem cell lines of the BM and this caused that it was recently administered in high doses within the conditioning regimen prior to allogeneic haematopoietic SCT in patients with haematological malignancies. 7 Despite the clinical use of the oral and i.v. formulation, pharmacokinetic data for adult patients are rather scarce.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Four patients experienced transient atrial fibrillation, which may be related to CYconditioning. 29 Patients over age 55 receiving CY-based conditioning regimens have been reported to experience a decrease in cardiac output, suggesting that high-dose CY in older patients may be associated with cardiac toxicity. 30 There are little published data on the outcomes of autologous SCT for patients more than the age of 70 years.…”
Section: Discussionmentioning
confidence: 99%
“…Some nonrandomized studies on the use of an intensified conditioning have reported better disease control for high-risk patients, but higher rates of toxicity and TRM have also been reported. [6][7][8] The search for alternative regimens to the standard BUCY2 aimed at reducing the relapse rate and also TRM has proven to be difficult. [9][10][11][12] Idarubicin (IDA, 4-demethoxydaunorubicin) was first introduced as a new anthracycline and now it has been widely used to treat AML or relapsed/refractory ALL because it is more effective in multidrug-resistant cell lines and has relatively low cardiotoxicity, but a high penetration rate to central nervous system, compared with DNR or doxorubicin.…”
Section: Introductionmentioning
confidence: 99%